Efficacy of the Orifice-Level Passive Ultrasonic Activation Technique in Removing Debris from Mandibular Molars: An Ex Vivo Study: Orifice-level ultrasonic activation and debris removal - Bolourchi, Iman; Zargar, Nazanin; Khosravi, Kamyar; Mashhadiabbas, Fatemeh; Akbarzadeh Baghban, Alireza; Pourmousavi, Leila (Journal of Lasers in Medical Sciences, 2024)
Introduction: This study aimed to evaluate the efficacy of the orifice-level passive ultrasonic activation (OL-PUA) technique in removing debris from the mesial root canals of mandibular molars, besides comparing it with other approaches, including manual dynamic agitation (MDA), EndoActivator, and laser-activated irrigation (LAI). Methods: Ninety mesial roots of mandibular molars were prepared up to 25.06 using the Race rotary system, filled with 3% sodium hypochlorite (NaOCl), and then they were randomly assigned to 5 groups (n=15) based on the activation protocol: MDA, EndoActivator, OL-PUA, LAI (using a diode laser), and needle irrigation (no activation). Moreover, one group served as the negative control using normal saline as the final irrigant. The roots were decalcified and sectioned into coronal, middle, and apical cross-sections. After histological staining, the remaining debris was assessed with an optical microscope and measured in the canals and isthmuses using histomorphometric analysis. Statistical analyses were performed by using one-way ANOVA and Tukey’s HSD post hoc test (P=0.05). Results: Although less residual debris was observed after OL-PUA/LAI than using the EndoActivator/ MDA methods, no significant difference was found between the four activation techniques at any root third (P>0.05). The OL-PUA/LAI group harbored significantly less remaining debris than the needle-irrigated samples at all root thirds (P<0.05). Debris accumulation increased from the coronal to the apical root thirds. Conclusion: No statistical difference was detected between the four activation techniques in terms of debris-removal performance, and none of them resulted in completely debris-free canals. Orifice-level PUA proved to be a promising approach with significant efficacy in removing debris compared to control groups.